Prevalence of Escherichia coli in Under-Five Children with Diarrhea in Ethiopia: A Systematic Review and Meta-Analysis - Tizazu Zenebe; Meseret Mitiku; Yonas Alem (International Journal of Microbiology)
Diarrhea remains as a high health burden, especially to children in low-income countries including Ethiopia. Diarrheagenic Escherichia coli have been commonly associated as bacterial pathogens causing diarrheal disease among children. This systemic review and meta-analysis was intended to determine the pooled prevalence of Escherichia coli in under-five children with diarrhea in Ethiopia. A comprehensive search in PubMed, Google Scholar, ScienceDirect, ResearchGate, and Google search engine and manual searching were done for this systematic review and meta-analysis. The eligibility criteria for selecting studies were studies involving under-five children with diarrhea in Ethiopia, published articles, cross-sectional studies, and articles reported in English. The study was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist. The data analysis was done using STATA 16.0 software. Cochran’s Q-test and I2 statistics were used for the assessment of heterogeneity. The random-effect model was used to estimate the pooled prevalence of Escherichia coli. A total of 797 articles were initially retrieved, and finally, 11 studies met the eligibility criteria and were included in the final meta-analysis. The pooled prevalence of Escherichia coli was 25% (95% CI: 9, 41). The pooled prevalence was varied by region, detection method, and sample size. The high prevalence emphasizes that Escherichia coli is a potential pathogen in under-five children with diarrhea in Ethiopia.